Unusual Causes of Abdominal Pain after Colonoscopy: A Case Series - Samsami, Dorsa; Sargon, Peter; Qazi, Baseer; Shapiro, Alan (Journal of Digestive Endoscopy, 2019)
Colonoscopy is a relatively safe procedure with an overall complication rate between 0.2 and 0.35%. Complications do occur, however, including preparation related complications, colonic perforation, postpolypectomy hemorrhage, postpolypectomy coagulation syndrome, and other less-common miscellaneous complications. Abdominal pain is one of the more common complaints that symptomatic patients will present with after a colonoscopy, occurring up to 5% of the time. Although the cause is usually minor and does not require further workup, gastroenterologists are most concerned about perforation and postpolypectomy coagulation syndrome in the setting of severe abdominal pain. However, as gastroenterologists, we must also be cognizant that there may be other less-common causes of the abdominal pain. The four cases presented here illustrate rare presentations of abdominal pain after colonoscopy, consisting of acute diverticulitis, incarcerated umbilical hernia, acute gangrenous cholecystitis, and rupture of the ovarian cyst.
Keywords: acute diverticulitis; acute gangrenous cholecystitis; colonoscopy; incarcerated umbilical hernia; rupture of ovarian cyst